IMPLEMENTASI KOMPETENSI PROFESIONAL GURU DALAM PENINGKATAN HASIL BELAJAR PESERTA DIDIK DI UPTD SD NEGERI 222 WAGE KECAMATAN SABBANGPARU KABUPATEN WAJO - Sitti Aminah; Ambo Upe Abbas; Besse Herlina; Andi Aryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the implementation of teachers' professional competencies in improving student learning outcomes at UPTD SD Negeri 222 Wage, Sabbangparu District, Wajo Regency. The professional competence of teachers includes the ability to master subject matter, scientific structure and methods, as well as the utilization of learning resources to support the learning process. The approach used is qualitative with a descriptive method, through data collection techniques such as observation, interviews, and documentation of teachers and students. The research results indicate that the implementation of teachers' professional competencies at the school has been quite good, marked by the teachers' ability to master and deliver the material in a systematic manner and in accordance with the characteristics of the students. Teachers have also implemented scientific methods and utilized learning resources, although there are obstacles such as limited learning media and high administrative burdens, which affect the effectiveness of improving learning outcomes. The novelty of this research lies in emphasizing the importance of continuous support to enhance learning competencies and facilities, as well as managing administrative burdens so that the learning process can run more optimally. The recommendations proposed include the need for continuous training, the provision of adequate learning facilities, and the reduction of teachers' administrative burdens, in order to encourage more effective and sustainable improvement in students' learning outcomes.